Comparative Study of Three Different Extenders on Fresh, Chilled and Cryopreserved Mafriwal Bullâ€™s Sperm - Amalina N, Nur; K, Asmad; I, Zawawi (International Journal of Engineering and Technology, 2018)
The aim of this study is to study the effects of different types of extender and to determine the effects of cryopreservation process (before chilling, after chilling, after cryopreservation) on sperm characteristics and sperm morphology of Mafriwal bulls. Three natural based extender (Aloe vera based extender (AVBX), honey based extender (HBX), egg yolk based extender (EYBX)) and a control (BioxcellÂ®) were used as extender and compared for different semen quality parameters that can be assessed under routine laboratory condition. Semen samples were collected from three sexually matured Mafriwal bulls by using artificial vagina (AV). Samples collected were subjected to four different treatments and was evaluated after dilution with extenders. After diluted, the samples were chilled for 2 hours in 4Â°C. The semen samples were then packed into 0.25 ml straw for further cryopreservation process. After 24 hours, the cryopreserved semen samples were evaluated. Eosin nigrosin smearing were done to evaluate sperm morphology. The EYBX resulted in the highest percentage of almost all parameters tested in the study followed by BioxcellÂ®, AVBX and HBX. Semen treated with EYBX and BioxcellÂ® shows no significant different (P>0.05). All treatment shows decrease of sperm characteristics after chilling and frozen-thawed but AVBX and HBX shows rapid depletion of sperm characteristics (P<0.05) after chilling process. This study suggests that EYBX is the most suitable extender for cryopreservation Mafriwal bullâ€™s semen. However, further study is warranted to investigate the optimum concentration of other raw materials (i.e. Aloe vera and honey) in extender for semen cryopreservation.Â